THE USE OF MODERN MULTIMEDIA RESOURCES IN THE PRACTICE OF SPORTS AND PHYSICAL EDUCATION - Vako, I. I.; Grygus, I. M.; Nikitenko, O. V. (Rehabilitation and Recreation, 2023)
The purpose of the study is to develop a multimedia project “DOMINI”, which involves building up the basics of hand-to-hand combat in young athletes. Methods: to achieve the goal, the authors used the analysis of documentary materials and qualimetry, i. e., expert assessments. Expert evaluation was carried out with the participation of 20 experts (coaches with more than 5 years of experience). The results of the expert evaluation laid the groundwork for developing the “DOMINI” multimedia project designed to build up the basics of hand-to-hand combat in young athletes. The elaboration of the multimedia project was driven by the transformation and rethinking of innovative scientific ideas. The advantages of resorting to the didactics of multimedia, in particular the multimedia project “DOMINI”, are as follows: the option of creating a coach’s original didactic product; accessibility for coaches to design and use the basic modules of the multimedia project; simultaneous involvement of several perception channels of the athlete in the learning process, which contributes to the integration of information received from several different sensory organs; stimulation of cognitive aspects of learning, i.e., perception and awareness of information; opening the door for independent work of young athletes; individualization of the training process; prospects for practicing remote communication via social networks and messengers; distribution of instructional material, presentations, videos, etc. The multimedia project “DOMINI” is a component of the training environment, an electronic tool aimed at building up the basics of hand-to-hand combat in young athletes, upon which the integrity of the didactic cycle of the pedagogical process is maintained by the arrangement of the information structure, and the ground of pedagogical activity is the interaction of the athlete with the multimedia environment. Using modern multimedia resources – the latest software, 3D images, modern graphics, and virtual reality – allows coaches to significantly expand the toolkit for the technical training of young athletes and conduct training sessions diversely and creatively.